2015
DOI: 10.1364/ol.40.003133
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling-induced giant Goos–Hänchen shift in quantum wells

Abstract: Tunneling-induced quantum interference experienced by an incident probe in the asymmetric double AlGaAs/GaAs quantum well (QW) structure can be modulated by means of an external control light beam and the tunable coupling strengths of resonant tunneling. These phenomena can be exploited to devise a novel intracavity medium to control Goos-Hänchen (GH) shifts of a mid-infrared probe beam incident on a cavity. For a suitably designed QW structure, our results show that maximum negative shift of 2.62 mm and posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 26 publications
(43 reference statements)
0
26
0
Order By: Relevance
“…l l 2 3 represents the cross-coupling term between levels 2 and 3 related to the tunneling effect from the electronic continuum 42 . Moreover, the parameter η γ γ = .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…l l 2 3 represents the cross-coupling term between levels 2 and 3 related to the tunneling effect from the electronic continuum 42 . Moreover, the parameter η γ γ = .…”
Section: Resultsmentioning
confidence: 99%
“…They found that the bistable threshold can be adjusted by using of intense laser field. The effect of tunneling induced quantum interference on optical properties of SQW nanostructure has also been studied recently [42][43][44][45][46] . Yang et al 42 , studied the tunneling induced giant Goos-Hanchen shift in SQW.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a lots of quantum optical effects have been observed in the past decades and within different physics systems, there is renewed interest in such time-dependent dynamic effects which may include solitons 1620 , creation of short pulses 2125 , and multiwave mixing processes in the ultraslow propagation regime 2628 , etc. 2931 . In particular, time-dependent coherent control of the optical response of certain media that exhibit electromagnetic induced transparency (EIT) 1315 has also triggered a flurry of interest mainly due to its potential applications in integrated optics and quantum information science.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetically induced transparency (EIT) [1], in coherent media have lead to many interesting phenomena such as fourwave mixing [2,3], optical bistability [4][5][6], superluminal light propagation [7] and others [8][9][10][11][12][13][14][15][16][17][18][19][20] in quantum and nonlinear optics. In the mention phenomena, enhanced Kerr nonlinearity due to its wide usages in nonlinear optics and quantum information science [21,22] have been interested for analyzing and studying in past few years [23][24][25].…”
Section: Introductionmentioning
confidence: 99%